The Effect of Repeated Immersion of Maxillary Acrylic Complete Denture Prosthesis in Sodium Hypochlorite Solution Before Trimming, in Controlling Microbial Load – a Randomized Controlled Trial. (Bangladesh Journal of Medical Science, 2025)
Objective Trimming of complete denture poses a risk of cross infection to the dental professionals performing the adjustment. The conventional disinfection protocol involves immersion of the denture in a 0.5% sodium hypochlorite solution for 20 minutes before starting the procedure. The present study seeks to assess the effectiveness of a revised disinfection protocol, which involves immersing dentures in a 1% sodium hypochlorite solution for one minute repeatedly between adjustment procedures, alongside the conventional disinfection protocol, in order to control microbial load. Materials and Methods hirty-six maxillary complete denture patients were randomly divided into two groups, Group I conventional disinfection protocol and Group II repeated immersion disinfection protocol. Initially swab was taken from the prosthesis in both the groups to determine the microbial load and they were then subjected to conventional disinfection protocol. Following this, dentures in Group I were subjected to three cycles of trimming and swabs were again collected. In Group II, prostheses were subjected to intermittent one minute immersion in 1% sodium hypochlorite before each trimming cycle. After completion of trimming process swabs were taken. Blood agar and Mac Conkey agar were used to identify the organisms. Results Pretest – Posttest comparison by Wilcoxon signed rank test revealed statistically significant reduction of Klebsiella, Staphylococci and Streptococci in both Group I and Group II. Comparison of percentage reduction of microbial load in Group I and Group II was done using Mann-Whitney U test. The repeated immersion protocol resulted in a statistically significant reduction of Streptococci and Klebsiella when compared to conventional protocol. Conclusion Repeated one minute immersion in 1% sodium hypochlorite before each denture trimming cycle is effective in controlling the microbial load. The study was registered as a randomised clinical trial in the Clinical Trial Registry- India and listed as CTRI/2024/04/065264 in April 2024 Clinical Relevance: -Microbial recontamination of the denture occurs during adjustment procedures due to multiple reinsertions. Hence short repeated immersion disinfection protocols are advantageous in reducing microbial count and thereby alleviates the risk of cross infection.BJMS, Volume: 24. Supplementary Issue 2025, Page : 85-94